If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3m + 7 = 35 Reorder the terms: 7 + 3m = 35 Solving 7 + 3m = 35 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 3m = 35 + -7 Combine like terms: 7 + -7 = 0 0 + 3m = 35 + -7 3m = 35 + -7 Combine like terms: 35 + -7 = 28 3m = 28 Divide each side by '3'. m = 9.333333333 Simplifying m = 9.333333333
| 8/5x=32 | | 5a+2=3a | | 3-18u=-4u-12 | | 5+45/9-6 | | -13x=-65 | | 2(4+3m)=7(m+2) | | (n-5)*8=40 | | n+44-29n= | | x-28=119 | | a-3.1=6.6-4a | | 20-35u=-u-48 | | 2(3x-1)=-6(3+9x) | | 4x+6x=55-3x | | 23p-13p= | | -4n-6m=15+m | | 2z+14=9z | | 1/5x=2 | | B-5.3=20 | | 2(4+3x)=7(x+2) | | -12x+17=-89 | | A-30=-23 | | -4(8-3x)=2x+8 | | 4/n=n/16 | | 1/4s=-1 | | 2x(x-8)=3(x+3) | | 3(2x-1)=-1+6x | | -5+n=10 | | 3z+15=8z | | 2x-3=4x-11 | | 12+n=-6 | | 1/4y=2 | | 14c-4c= |